PENINGKATAN HASIL BELAJAR SISWA MATERI LIMBAH LUNAK MELALUI MEDIA PEMBELAJARAN CARTA - Surandini Wahyu Widi Mulyani (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2019)
Learning requires extensive knowledge in this matter of soft waste material. The purpose of this study is to improve student learning outcomes through learning media. The research method used in this study is a classroom action research method with 2 cycles. The study was conducted at Junior High School 1 Tambun Selatan 1, Bekasi in January - March 2019. The results showed that there was an increase in student learning outcomes seen from the gain score. Learning to use charts is now making students more enthusiastic in learning. This causes an increase in learning outcomes. The conclusion of this study is that media chart has succeeded in improving learning outcomes.